Parallel genome-wide screens identify synthetic viable interactions between the BLM helicase complex and Fanconi anemia - Martin Moder (Nature Portfolio, 2017)
Fanconi anemia is a complex disease affecting multiple DNA repair proteins that resolve DNA crosslinks which can block vital processes. Here the authors use parallel genome-wide screens that identify the BLM helicase complex as a suppressor of Fanconi anemia phenotypes.